2002
DOI: 10.1002/etc.5620210521
|View full text |Cite
|
Sign up to set email alerts
|

Use of ethylenediaminetetraacetic acid in pulp mills and effects on metal mobility and primary production

Abstract: Over the last decade, the use of ethylenediaminetetraacetic acid (EDTA) has increased by a factor of three within the Swedish pulp industry. The effects of pulp mill wastewater in combination with EDTA on metal mobility and the consequences for ecologically relevant organisms have been studied. Ethylenediaminetetraacetic acid was added to pulp mill effluent water in the laboratory and compared to wastewater without EDTA. Degradation of the water was followed over a experimental period up to eight weeks and sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The results of experiment 4 also indicate that growth of Ceramium from the Bothnian Sea may be regulated by deficiency of certain ions, rather than by osmotic stress in ambient water (Kirst 1990). To some extent, the observed outcome may reflect treatment effects, as the treatments media of very low salinity were not natural waters, but were prepared from dilution of brackish sea water with distilled water of a different ionic composition, or the added EDTA or some other component in the trace element solution may have stimulated growth directly (Eklund et al 2002). However, none of this alternatives would explain the observed differences in responses among isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The results of experiment 4 also indicate that growth of Ceramium from the Bothnian Sea may be regulated by deficiency of certain ions, rather than by osmotic stress in ambient water (Kirst 1990). To some extent, the observed outcome may reflect treatment effects, as the treatments media of very low salinity were not natural waters, but were prepared from dilution of brackish sea water with distilled water of a different ionic composition, or the added EDTA or some other component in the trace element solution may have stimulated growth directly (Eklund et al 2002). However, none of this alternatives would explain the observed differences in responses among isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory assay was performed using simultaneously plain site waters and site waters enriched with the same nutrients comprising the MBL. Because growth differences when performing a microalgal assay on natural water samples may be due to toxicity, nutrient shortage, or both, it is a recommended approach for laboratory algal assays evaluating the hazard of natural samples (e.g., effluents) to add nutrients to the test waters (Environment Canada, 1992;USEPA, 1994;Eklund et al, 2002). In this way, nutrient differences among waters are eliminated and it is possible to distinguish a toxic effect from that caused by poor nutrient levels.…”
Section: Laboratory Bioassaymentioning
confidence: 99%
“…Liu et al [23] reported 5 to 10 mg/L of Ni in a deplating wastewater. In the pulp and paper industries, Ni concentrations of 0.030 mg/L were detected in the present study (Table 2), and a concentration of 0.001 mg/L was found in a Swedish pulp and paper mill effluent [24]. Thus, compared with other industries, the amount of Ni discharged from pulp and paper mills is relatively low.…”
Section: Discussionmentioning
confidence: 50%